Effect of Albendazole at different concentrations on fertilization and early cleavage in Tetrapygus niger “sea urchin” (Scientia Agropecuaria, 2013)
In this study we evaluated the effect of Albendazole at different concentrations and exposure times on the process of fertilization and early cleavage in Tetrapygus niger "sea urchin". Each experimental group consisted of 200 mL, of previously filtered seawater at pH 7.3 and temperature of 20 ± 2 °C, plus five drops of eggs and two drops of spermatozoa exposed to different concentrations of Albendazole 400 ppm, 800 ppm and 1200 ppm. Determining the effect of Albendazole was conducted by counting the number of cones of fertilization, as well as the number of cleaving embryos with normal and abnormal. The ANOVA and multiple comparison test Tukey averages showed significant differences between the treatments, namely that increasing the concentration of Albendazole fertilization rate decreases and increases the percentage of embryos with abnormal cleavage, so therefore concluded that the Albendazole at different concentrations and exposure times affects the process of fertilization and early cleavage in T, niger "sea urchin".
Keywords: Albendazole; fertilization; early cleavage; Tetrapygus niger